Management Taman Pendidikan Al-Qur’an Mushollah Nurul Khoirot Desa Tanjung Tambak Kecamatan Tanjung Batu Kabupaten Ogan Ilir - Mukti Ali (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This study discusses the efforts made by TPA Mushollah Nurul Khoirot in reducing illiteracy in reading and writing the Qur'an as well as the opportunities and challenges faced by TPA Mushollah Nurul Khoirot in reducing illiteracy in reading and writing the Qur'an in children in Tanjung Tambak village. Tanjung Batu district, Ogan Ilir district. This research is a descriptive or qualitative research. Qualitative research method is a method used to examine the condition of natural objects. In this method, the researcher uses a communication approach and a management approach. The object in this study is the founder of TPA Mushollah Nurul Khoirot. Data collection techniques used are observation, in-depth interviews and documentation. The results show that the management of TPA Mushollah Nurul Khoirot can be said to be good, this can be seen from the management functions that have been managed which consist of: 1) planning in determining goals 2) organizing in determining activities and organizational structures 3) implementation in terms of providing motivation to establish relations and communication 4) supervision in terms of setting standards, comparing activities carried out with standards and taking corrective actions. The implication of this research is that the government must pay special attention and then the place must be designed to attract children's interest, encouragement and motivation from parents to direct their children to be more active in deepening religious knowledge and students are expected to have the desire to be able and want to be able to read and practice the Qur'an.